中国对澜沧江和下湄公河流域水电发展的影响 - Matthews, Nathaniel; Motta, Stew (CGIAR Challenge Program on Water and Food, 2013)
Reviews the history of Chinese hydropower development on the Lancang from the 1950s to the present, the downstream political, economic and environmental implications of Lancang hydropower, China’s hydropower influence in the Lower Mekong Basin, and China’s external environmental and social policies related to hydropower.